The biodiversity of macroalgae in the coastal waters of Blongko Village, Sub-District of Sinonsayang, District of South Minahasa - Kepel, Rene Charles; Mantiri, Desy M. H.; Rumengan, Anton; Nasprianto, . (Jurnal Ilmiah PLATAX, 2018)
This study was carried out in coastal waters of Blongko Vilage, Sub-District of Sinonsayang, District of South Minahasa with an objective of knowing the taxa composition of macroalgae through morphological studies. Data collection used exploring survey. Results found 14 species that consisted 8 species of green algae, 2 species of brown algae, and 4 species of red algae.Keyword: Macroalgae, Blongko. Â AbstrakÂ Penelitian ini dilakukan di perairan pesisir Blongko, Kecamatan Sinonsayang, Kabupaten Minahasa Selatan dengan tujuan untuk mengetahui komposisi taksa makroalga melalui pendekatan morfologi. Pengambilan data dilakukan dengan menggunakan metode Survei Jelajah. Hasil penelitian menemukan 14 spesies, yang terdiri dari 8 spesies alga hijau, 2 spesies alga cokelat dan 4 spesies alga merah.Kata Kunci: makroalga, Blongko.